2011
DOI: 10.1021/ja207853e
|View full text |Cite
|
Sign up to set email alerts
|

Single-Pixel, Single-Layer Polymer Device as a Tricolor Sensor with Signals Mimicking Natural Photoreceptors

Abstract: Color sensing procedures typically involve multiple active detectors or a photodetector coupled to a filter array. We demonstrate the possibility of using a single polymer layer based device structure for multicolor sensing. The device structure does not require any color filters or any subpixelation, and it distinguishes colors without any external bias. The color sensing relies on an appropriate thickness of the active polymer layer that results in a characteristic polarity and temporal profile of the photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…[ 248 ] 3.3.2.1. Pixelated Multilayer (Stacked) OPD Color Imaging : As previously discussed, Higashi et al and Lamprecht et al introduced extra layers into the OPD devices to absorb wavelengths outside the desired spectral window to give a narrower response.…”
Section: Reviewmentioning
confidence: 99%
“…[ 248 ] 3.3.2.1. Pixelated Multilayer (Stacked) OPD Color Imaging : As previously discussed, Higashi et al and Lamprecht et al introduced extra layers into the OPD devices to absorb wavelengths outside the desired spectral window to give a narrower response.…”
Section: Reviewmentioning
confidence: 99%
“…The former option has been the predominant strategy for inorganic semiconductor-based narrowband photodetection 3 . However, such a strategy complicates the design of the image sensor and can also lead to degradation of the picture quality and colour constancy [4][5][6][7][8] . The molecular nature of organic semiconductors means that organic photodiodes (OPDs) can be designed with relatively narrow spectral responses of o200 nm full-width-at-half-maximum (FWHM) and respectable EQEs (10-30%), but the suppression of response outside the chosen spectral window still remains a significant constraint 8 .…”
mentioning
confidence: 99%
“…In particular, oxygen and aqueous solutions may have a negative effect, such as degradation and quenching species. Examples for two photovoltaic polymeric mixtures, which were tested and found stable in aqueous solution conditions include: poly(3-octylthiophene): N2200 (P3OT:N2200) 125 and poly(3-hexylthiophene): phenyl-C61-butyric-acid-methyl ester (P3HT:PCBM). 126 Ghezzi et al 127 demonstrated photostimulation of neurons by a polymeric mixture-based scheme (P3HT:PCBM), illustrated in Figure 2.…”
mentioning
confidence: 99%